Epoxy-modified Portland Cement: Effect of the Resin Hardener on the Chemical Degradation by Carbon Dioxide. (July 2017) - Baldissera, Alessandra F.; Schütz, Marta K.; Vecchia, Felipe D.; Seferin, Marcus; Ligabue, Rosane; Menezes, Sonia C.; Einloft, Sandra
Abstract: Portland cement employed in CO2 injection wells is strongly susceptible to acidic attacks leading to long-term deterioration. This study investigates the chemical degradation of composites based on an epoxy resin blend (with and without a hardener) and cement paste when exposed to CO2, aiming to provide a new polymer-modified cement with better chemical resistance. CO2 degradation experiments were conducted with dissolved CO2 at 70 °C and 50 bar. Results showed that composites containing hardener undergo lower degradation by CO2 when compared to the composites with uncured epoxy resins. Some of these composites present smaller degraded layer than pure Portland cement.